Maternal health profile of children with severe acute malnutrition admitted in NRC’s of Bhopal - Bhatia, Padma; Sethia, Soumitra; Melwani, Veena; Gupta, Mahesh; Priya, Angelin; Singh, Daneshwar (International Journal Of Community Medicine And Public Health, 2018)
Background: Protein energy malnutrition is the most widely prevalent form of malnutrition among under-five children. Factors responsible for malnutrition in India comprise of low birth weight, maternal health problems, delay in introduction of complementary feeds, faulty child care and other poor environmental conditions. This study aims to evaluate the health status of mothers of severe acute malnutrition (SAM) children admitted in three NRC’s of Bhopal. Methods: A cross-sectional record based study was done on mothers of 255 children up to 5 year of age who were admitted with SAM in the three NRC of Bhopal district. Details were filled in a questionnaire. The body mass index (BMI) was calculated and graded according to the WHO classification. Results: The mean age of study participants was 24.8 years, mean BMI was 18.5, mean Hb was 10.4 g/dl. According to the BMI, 147 (57.7%) of the mothers were underweight, out of them 43 (16.8%) were severely thin. Anemia was present in 90% mothers, out of which 80% were moderately anemic and 11 (4.3%) was severely anemic, anemia and BMI of mothers have a significant correlation. At the time of the study, 65 (26%) mothers had more than two children and 113 mothers had two children. Conclusions: The health status of mothers indicates that they are undernourished and anemic with lower parity and age. It is therefore recommended that during the 14-21 day stay of SAM child maternal nutrition should be emphasized upon along with counselling sessions.